Multi-Omics Analysis Based on Genomic Instability for Prognostic Prediction in Lower-Grade Glioma - Cao, Yudong; Zhu, Hecheng; Liu, Weidong; Wang, Lei; Yin, Wen; Tan, Jun; Zhou, Quanwei; Xin, Zhaoqi; Huang, Hailong; Xie, Dongcheng; Zhao, Ming; Jiang, Xingjun; et al. (Frontiers in Genetics, 2022)
Background: Lower-grade gliomas (LGGs) are a heterogeneous set of gliomas. One of the primary sources of glioma heterogeneity is genomic instability, a novel characteristic of cancer. It has been reported that lncRNAs play an essential role in regulating genomic stability. However, the potential relationship between genomic instability and lncRNA in LGGs and its prognostic value is unclear. Methods: In this study, the LGG samples from The Cancer Genome Atlas (TCGA) were divided into two clusters by integrating the lncRNA expression profile and somatic mutation data using hierarchical clustering. Then, with the differentially expressed lncRNAs between these two clusters, we identified genomic instability-related lncRNAs (GInLncRNAs) in the LGG samples and analyzed their potential function and pathway by co-expression network. Cox and LASSO regression analyses were conducted to establish a genomic instability-related lncRNA prognostic signature (GInLncSig), which was assessed by internal and external verification, correlation analysis with somatic mutation, independent prognostic analysis, clinical stratification analysis, and model comparisons. We also established a nomogram to predict the prognosis more accurately. Finally, we performed Multi-omics based analyses to explore the relationship between risk scores and multi-omics data, including immune characteristics, N6-methyladenosine (m6A), stemness index, drug sensitivity, and gene set enrichment analysis (GSEA). Results: We identified 52 GInLncRNAs and screened five from them to construct the GInLncSig model (CRNDE, AC109439.1, AL390755.1, AC092957.1, HOXD-AS2), which could independently and accurately predict the outcome of patients with LGG. The GInLncSig model was significantly associated with somatic mutation and outperformed other published signatures. GSEA revealed that metabolic pathways, immune pathways, and cancer pathways were enriched in the high-risk group. Multy-omics based analyses revealed that T cell functions, m6A statuses, stemness characteristics were significantly disparate between two risk subgroups, and immune checkpoints such as PD−L1, PDCD1LG2, and HAVCR2 were significantly highly expressed in the high-risk group. The expression of GInLncSig prognostic genes dramatically correlated with the sensitivity of tumor cells to chemotherapy drugs. Conclusion: A novel signature composed of five GInLncRNAs can be utilized to predict prognosis and impact the immune status, m6A status, stemness characteristics in LGG. Furthermore, these genes may be potential and alternative therapeutic targets.